A Review Paper on The Effect of Waste Paper on Mechanical Properties of Concrete - Solahuddin, Azuwa; Fadzil, Mat Yahaya (IOP Publishing, 2021)
Cement, sand, coarse aggregate and water are the materials to make concrete. The waste paper has been dumped as waste and causes environmental pollution behind mill or landfill. The industry paper wastage for every year is increasing gradually. More spaces are being needed for landfills, uses energy loss of natural resources and increase of expenditure and various types of pollutions. Utilizing waste paper as cement replacement or addition in concrete production will reduce environmental pollutions. This review paper is to investigate the effect of waste paper on mechanical properties of concrete such as compressive strength and flexural strength. From many previous studies before this, 5% and 10% waste paper as cement replacement and additions were the ideal percentages to increase the compressive and flexural strengths of concrete. This study indicates waste paper can give benefit by using it as additional material in concrete production.